Comparative evaluation of two commercially available desensitizing agents for the treatment of dentinal hypersensitivity - Nymphea Pandit; Rajan Gupta; Aarti Bansal (Indian Journal of Dental Research, 2012)
Aims: A randomized clinical trail was designed to compare the efficacy of two commercially available desensitizing agents (fluoride varnish containing 6% sodium fluoride and 6% calcium fluoride and a gel containing 6% potassium nitrate and 0.11% fluoride ions) in the treatment of dentinal hypersensitivity. Settings and Design: Randomized clinical trial. Materials and Methods: Twenty-one patients were selected. Subjects were evaluated using three different stimuli, i.e., tactile test, air blast test and cold water test. They were then randomly divided into two groups. Patients in group I were treated with fluoride varnish and group II patients were treated with gel containing 6% potassium nitrate and 0.11% fluoride ions. The patients were examined at baseline, immediately after application of the agent, at 1 week, 1 month and 3 months interval. Statistical Analysis: Statistical analysis was done using unpaired "t" test, paired "t" test and Chi-square test with Yate′s correction. Results: The results were analyzed; it was seen that patients treated in group I showed significantly better results compared to group II patients at 1 month and 3 months interval. Teeth which required repeat dose and those which did not require repeat dose were comparable in number. Conclusions: Both the agents showed significant reduction in sensitivity at all time intervals compared to baseline. A comparatively significant reduction in sensitivity score was seen in patients treated with fluoride varnish and it appeared to be more effective in providing long-term relief against all the three test stimuli. Teeth with initial high sensitivity score required repeat doses, which was comparable for both the groups.